Identification and quantification of different species in animal fibres by LC/ESI‐MS analysis of keratin‐derived proteolytic peptides. (10th July 2013) - Paolella, Sara; Bencivenni, Mariangela; Lambertini, Francesca; Prandi, Barbara; Faccini, Andrea; Tonetti, Cinzia; Vineis, Claudia; Sforza, Stefano
Abstract : In the present paper, a proteomic method for species determination in fibres has been developed. Keratin was extracted from yak, wool and cashmere fibres and digested by trypsin, providing peptide mixtures that were analyzed by liquid chromatography coupled with electrospray mass spectrometry (LC/ESI‐MS) in order to identify peptidic species‐specific markers able to differentiate the fibres. Several suitable peptide markers were identified and validated in different fibres of different origin and having undergone different technological treatments, showing 100% specificity and 100% selectivity. Most of the peptide markers were also identified by means of high‐resolution mass spectrometry, confirming the origin from species‐specific keratin sequences. Some peptides were also used for the quantification of the different species in mixed fibres by LC/ESI‐MS. Validation experiments and blind tests confirmed their ability to act as very specific quantitative and qualitative markers. The method here developed is a valid complement to the standard benchmark methods for fibre identification and quantification and will be very useful for assessing the authenticity of textile products. Copyright © 2013 John Wiley & Sons, Ltd.